Implementation of Sobat Dukcapil Application Services in The Tangerang City - Septia Kurnia Sari (PT ARRUS Intelektual Indonesia, 2023)
Constitutes an attempt to ensure that public services are realized such that they can be maintained under any circumstances. Through the Sobat Dukcapil Application, Department of Population and Civil Registration in the Tangerang City is attempting to develop an online population administration service that the general public can use whenever and wherever they choose, with no daily submission cap. Charles O. Jones theory, which suggests there are three key indicators that may be used to provide a more complete picture of implementation policies, is the hypothesis that this study is based on. The purpose is to give a general summary of how the Sobat Dukcapil Application is services have been implemented in Tangerang City. The method is used a descriptive research this study. The Sobat Dukcapil Application is services have been implemented in Tangerang City, according to the study is results, but they have not been particularly successful because the neighborhood continues to have a number of issues. In order to improve the quality of service provided by the Sobat Dukcapil Application and make it easier for the general public to use. This occurs to ensure that the community is grateful for the services offered by the Sobat Dukcapil Application.